Grammars of the Urban Ground - Amin, Ash; Lancione, Michele (Duke University Press, 2022)
The contributors to Grammars of the Urban Ground develop a new conceptual framework and vocabulary for capturing the complex, ever-shifting, and interactive processes that shape contemporary cities.